Telaah Buku Ajar Bahasa Arab Madrasah Aliyah Kelas X Berdasarkan Keputusan Menteri Agama (KMA) Nomor 183 Tahun 2019 - Chicin Marchella Kolintama; Muhammad Nur Iman (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2022)
This article aims to determine the feasibility of Arabic books to be used as a guide for the Madrasah Aliah education unit for class X students in understanding Arabic materials. The research method used is library research, namely collecting data and analyzing library sources. The results of the analysis show that most of the material which consists of 6 chapters and each chapter has four basic skills that must be mastered by students is suitable for use because it is in accordance with the objectives of Core Competence (KI) and Basic Competence (KD). In Chapters 1 to 4, conformity with Core Competencies (KI) and Basic Competencies (KD) is found in the four skills in Arabic, as for Chapter 5 and Chapter 6 conformity with the objectives of Core Competencies (KI) and Basic Competencies (KD) there are on three of the four skills in Arabic. Keywords: Review, Textbooks, Curriculum, Arabic.